The role of business incubator on cultivating innovation on start-ups: The case study of Bandung techno park (BTP) Indonesia - Tricahyono, Dodie; Turipanam Alamanda, Dini; Anggadwita, Grisna; S.A Prabowo, Fajar; Yuldinawati, Lia (International Journal of Engineering and Technology, 2018)
The importance of business incubators to support the growth of start-ups cannot be overemphasized especially in developing country such as Indonesia. This study aims to determine the most appropriate model that competent to provide an accurate depiction of the role of a business incubator on cultivating innovation of startups during the incubation process. It is conducted by using a case of Bandung Techno Park (BTP) as one of the first business incubators in Indonesia that positioned itself as an incubator for technology-based start-ups. The data were collected by ensuring the credibility, transferability, dependability, and conformability by adopting triangulation as the primary method. Informants were recruited from different stakeholder groups and provided with the opportunity to verify the result of the interviews. The findings show that there are none of the existing models that are able to provide a complete yet accurate depiction of BTP functioning. Almost all of the models suffer from lack of means to accommodate the learning process that must be undergone by start-ups during the incubation process. In order to respond to this gap, this study offered minimum requirements that must be satisfied by any incubator models. Â